The antitumor effect of tanshinone IIA on anti-proliferation and decreasing VEGF/VEGFR2 expression on the human non-small cell lung cancer A549 cell line - Jun Xie; Jiahui Liu; Heng Liu; Shihui Liang; Meigui Lin; Yueyu Gu; Taoli Liu; Dongmei Wang; Hui Ge; Sui-lin Mo (Elsevier, 2015)
The effects of tanshinone IIA on the proliferation of the human non-small cell lung cancer cell line A549 and its possible mechanism on the VEGF/VEGFR signal pathway were investigated. The exploration of the interaction between tanshinone IIA and its target proteins provides a feasible platform for studying the anticancer mechanism of active components of herbs. The CCK-8 assay was used to evaluate the proliferative activity of A549 cells treated with tanshinone IIA (2.5−80 μmol/L) for 24, 48 and 72 h, respectively. Flow cytometry was used for the detection of cell apoptosis and cell cycle perturbation. VEGF and VEGFR2 expression were studied by Western blotting. The binding mode of tanshinone IIA within the crystal structure of the VEGFR2 protein was evaluated with molecular docking analysis by use of the CDOCKER algorithm in Discovery Studio 2.1. The CCK-8 results showed that tanshinone IIA can significantly inhibit A549 cell proliferation in a dose- and time-dependent manner. Flow cytometry results showed that the apoptosis rate of tested group was higher than the vehicle control, and tanshinone IIA-treated cells accumulated at the S phase, which was higher than the vehicle control. Furthermore, the expression of VEGF and VEGFR2 was decreased in Western blot. Finally, molecular docking analysis revealed that tanshinone IIA could be stably docked into the kinase domain of VEGFR2 protein with its unique modes to form H-bonds with Cys917 and π-π stacking interactions with Val848. In conclusion, tanshinone IIA may suppress A549 proliferation, induce apoptosis and cell cycle arrest at the S phase. This drug may suppress angiogenesis by targeting the protein kinase domains of VEGF/VEGFR2.